BIOETANOL DARI NIRA NIPAH KENTAL SECARA NIR-SINAMBUNG (BATCH) DENGAN PENAMBAHAN Cordyceps mycelium POWDER DAN UREA - Sadzvirani, Sastiana; Restuhadi, Fajar; Rossi2, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research implemented to see the effect of combined treatment of urea and Cordyceps mycelium powder contain ergosterol with bioethanol fermentation from very high gravity Nypa sap in batch fermentation. This research implemented in an experimental method with two factors. The first factor is the levels of the source N as urea consist of four levels namely (U) (0.0; 0.2; 0.4; 0.6) gr/l and the second factor is the levels of the Cordyceps mycelium powder consist of three levels namely (C) (0.0; 0.5; 1.0) gr/l, so that obtained twelve combination of treatments without repetition. Analysis implemented every day including : levels of ethanol, levels of reduce sugar content, the number of microbial cells Saccharomyces cerevisiae and the degree of acidity (pH). Data were analyzed descriptively by use tabulations and charts. The best combination treatment was U4C2 (urea 0.6 gr/l and Cordyceps myceliumpowder 0.5 gr/l) which produced ethanol 31.5%. Keywords: Very high gravity nypa sap, Urea, Cordyceps mycelium powder, Bioethanol